2002
DOI: 10.1097/00022744-200206000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Genetic alteration and loss of expression of tumor suppressor gene PTEN has been found in carcinomas of the breast, prostate, and endometrium, as well as in gliomas. PTEN expression in neural crest/neuroendocrine (NC/NE) tissues and in neoplasms has not been reported. This study examines PTEN expression in embryonal, fetal, and adult tissues by immunohistochemistry. The authors found high PTEN expression in embryonal, fetal, and adult NC/NE tissues. The authors also study the PTEN expression in NC/NE neoplasms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Most carcinoids express PTEN but over half of poorly differentiated GEP demonstrate loss of PTEN (Wang et al 2002), and altered subcellular localization of PTEN has also been reported in islet cell carcinoma (Perren et al 2000). In this study, cytoplasmic PTEN expression was associated with a response to therapy in the entire patient cohort (PZ0.05), and this association was maintained when confined to patients receiving only systemic chemotherapy (PZ0.04).…”
Section: Discussionsupporting
confidence: 60%
“…Most carcinoids express PTEN but over half of poorly differentiated GEP demonstrate loss of PTEN (Wang et al 2002), and altered subcellular localization of PTEN has also been reported in islet cell carcinoma (Perren et al 2000). In this study, cytoplasmic PTEN expression was associated with a response to therapy in the entire patient cohort (PZ0.05), and this association was maintained when confined to patients receiving only systemic chemotherapy (PZ0.04).…”
Section: Discussionsupporting
confidence: 60%
“…The functional activation of the PI3K/AKT/mTOR signaling pathway has never been extensively investigated in the spectrum pulmonary or other NETs, except for indirect evidence of the expression of functionally related molecules such as PTEN (Wang et al 2002), tuberous sclerosis complex (TSC; Yao 2007), AKT (Shah et al 2006), and IGF1R (von Wichert et al…”
Section: Discussionmentioning
confidence: 99%
“…Recent insights revealed a significant complexity of the mTOR pathway that seems to cross talk with other well-characterized signaling cascades, thus paving the way for the use of combined therapies (Bjornsti & Houghton 2004, Guertin & Sabatini 2007, Meric-Bernstam & Gonzalez-Angulo 2009. mTOR signaling pathway can be upstream activated -most commonly via the PI3 kinase (PI3K)/AKT pathwayby receptors such as somatostatin receptors (SSTRs) or insulin-like growth factor receptor 1 (IGF1R) or by loss of inhibiting molecules, such as PTEN (von Wichert et al 2000, Wang et al 2002. Rapamycin (Sirolimus, Wyeth, Philadelphia, PA, USA) and its derivates are immunosuppressive macrolides that specifically block mTOR signaling and have been shown to possess anti-proliferative activity in a variety of malignancies both in vitro (Zitzmann et al 2007, Grozinsky-Glasberg et al 2010, Missiaglia et al 2010 and in phase II clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…Estimates suggest that activating mutations in one or another PI(3)K-Akt-mTOR pathway component account for up to 30% of all human cancers and this has been associated with poor prognosis (Luo et al 2003, Sawyers 2006. Lost expression of the PI(3)K inhibitor PTEN and aberrant activity of Akt and mTOR have been observed in different neuroendocrine tumors (NETs) of heterogeneous origin (Wang et al 2002, Shah et al 2006, Kasajima et al 2011. Akt is the primary effector of PI(3)K-generated phosphatidylinositol (3,4,5)-trisphosphate, thus being a principle mediator of growth factor-induced signal transduction.…”
Section: Introductionmentioning
confidence: 99%